2015
DOI: 10.1038/srep11352
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen anomaly in near surface carbon dioxide reveals deep stratospheric intrusion

Abstract: Stratosphere-troposphere exchange could be enhanced by tropopause folding, linked to variability in the subtropical jet stream. Relevant to tropospheric biogeochemistry is irreversible transport from the stratosphere, associated with deep intrusions. Here, oxygen anomalies in near surface air CO2 are used to study the irreversible transport from the stratosphere, where the triple oxygen isotopes of CO2 are distinct from those originating from the Earth’s surface. We show that the oxygen anomaly in CO2 is obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
67
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(71 citation statements)
references
References 68 publications
(104 reference statements)
4
67
0
Order By: Relevance
“…This value of λ o is chosen because it corresponds to the fractionation that occurs in transpiration (Landais et al, 2006) at an average relative humidity of 75% (more details about the choice of λ values are given in the Supplementary Material). With this selection of λ, the formulation of the partitioning of the tripleoxygen isotopes of CO 2 coming from exchanges with diverse waters (meteoric, vapor, soil, stem, and leaf) can be simplified since the triple isotope variations in these processes have similar λ values as λ o (Landais et al, 2006;Liang and Mahata, 2015). As a result, the oxygen isotope anomaly as defined below remains unchanged despite isotopic fractionation associated with oxygen transfer.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This value of λ o is chosen because it corresponds to the fractionation that occurs in transpiration (Landais et al, 2006) at an average relative humidity of 75% (more details about the choice of λ values are given in the Supplementary Material). With this selection of λ, the formulation of the partitioning of the tripleoxygen isotopes of CO 2 coming from exchanges with diverse waters (meteoric, vapor, soil, stem, and leaf) can be simplified since the triple isotope variations in these processes have similar λ values as λ o (Landais et al, 2006;Liang and Mahata, 2015). As a result, the oxygen isotope anomaly as defined below remains unchanged despite isotopic fractionation associated with oxygen transfer.…”
Section: Introductionmentioning
confidence: 99%
“…O value of a sample of CO 2 was ~0.01‰ (1-σ standard deviation), and the accuracy was also ~0.01‰ (see Liang and Mahata, 2015;Mahata et al, 2016). The uncertainty in δ O analysis) were 0.06‰ (e.g., see Liang and Mahata, 2015;.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In summer and fall Taiwan is significantly affected by typhoons, making the weather more dynamic and highly turbulent. All of these meteorological conditions make this region a possible site for stratospheric air incursion down to ground and sea levels (Liang and Mahata 2015). The Taipei basin has a particularly shallow boundary mixed layer in the winter (~500 m in daytime) (Chou et al 2007) which is generally lower than the surrounding mountains (~1000 m to the north and southeast), making the air mass confined and isolated in the basin for about a week.…”
Section: Introductionmentioning
confidence: 99%
“…The results from a phase correlation study of O 3 and CO supported this conclusion and suggested that the stratosphere-troposphere exchange carries stratospheric air into the troposphere at select places (Liang et al 2008b). This would be especially important in regions where intrusion events like typhoons/monsoons occur frequently (such as Taiwan), and the magnitude of the anomaly could be enhanced during those episodes (Liang and Mahata 2015).…”
Section: Introductionmentioning
confidence: 99%